U-Shaped Association Between Serum Uric Acid and Hemorrhagic Transformation After Intravenous Thrombolysis - Cheng, Zicheng; Zhan, Zhenxiang; Fu, Yaming; Zhang, Wen Y.; Xia, Lingfan; Xu, Tong; Chen, Hongfang; Han, Zhao (Current Neurovascular Research, 2022)
Background: Uric acid (UA) has both antioxidative and pro-oxidative properties. The study aimed to investigate the relationship between serum UA and hemorrhagic transformation (HT) after intravenous thrombolysis in patients with acute ischemic stroke. Methods: The patients undergoing intravenous thrombolysis from two hospitals in China were retrospectively analyzed. HT was evaluated using computed tomography images reviewed within 24- 36h after thrombolysis. Symptomatic intracranial hemorrhage (sICH) was defined as HT accompanied by worsening neurological function. Multivariate logistic regression and spline regression models were performed to explore the relationship between serum UA levels and the risk of HT and sICH. Results: Among 503 included patients, 60 (11.9%) were diagnosed with HT and 22 (4.4%) developed sICH. Patients with HT had significant lower serum UA levels than those without HT (245 [214-325 vs. 312 [256-370] μmol/L, p < 0.001). Multivariable logistic regression analysis indicated that patients with higher serum UA levels had a lower risk of HT (OR per 10-μmol/L increase 0.96, 95%CI 0.92–0.99, p = 0.015). Furthermore, multiple-adjusted spline regression models showed a Ushaped association between serum UA levels and HT (p < 0.001 for non-linearity). Similar results were present between serum UA and sICH. Restricted cubic spline models predicted the lowest risk of HT and sICH when the serum UA levels were 386μmol/L. Conclusion: The data show the U-shaped relationship between serum UA levels and the risk of HT and sICH after intravenous thrombolysis.
Keywords: hemorrhagic transformation